Case Report: Neoadjuvant PD-1 Blockade Plus Concurrent Chemoradiotherapy in Unresectable Locally Advanced Gastric Cancer Patients - Wei, Jia; Lu, Xiaofeng; Liu, Qin; Li, Lin; Liu, Song; Liu, Fangcen; Fu, Yao; Fan, Xiangshan; Yang, Yang; Qi, Chuang; Yu, Yangyang; Guan, Wenxian; et al. (Frontiers in Oncology, 2021)
Programmed death 1(PD-1) bolckade has shown promising efficacy in advanced gastric cancer. Here, we performed a retrospective analysis of three patients with locally advanced gastric cancer who received adjuvant PD-1 plus chemoradiotherapy as neoadjuvant treatment. Neoadjuvant sintilimab plus concurrent chemoradiotherapy had an acceptable side-effect profile. All three patients underwent surgical gastrectomy after a median of 3.9 months. A major pathological response occurred in two resected tumors and a pathologic complete response was observed in one patient. Our results suggest that PD-1 blockade combined with chemoradiotherapy is a promising strategy as a neoadjuvant therapy in patients with unresectable locally advanced gastric cancer.